1985
DOI: 10.1007/bf01908180
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic ischaemic cardiac arrest of the isolated perfused rat heart: effects of trifluoperazine and lysolecithin on mechanical and metabolic recovery

Abstract: To evaluate the hypothesis that maintenance of the integrity of myocardial membrane systems and prevention of Ca2+ influx into the cell are significant in the survival of ischaemic tissue, the effect of trifluoperazine and lysolecithin, were tested on the recovery of globally ischaemic rat hearts. Trifluoperazine increases membrane stabilization, inhibits calmodulin and binds to other Ca2+-dependent proteins. Lysolecithin, on the other hand, has a detergent action on myocardial cell membranes and facilitates C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…However, the effects of fatty acids on liver metabolism are multiple and difficult to disentangle at present (see Schonfeld et al, 1988;Nobes et al, 1990b). Lochner et al (1981) found that increased content of acyl-CoA in isolated rat hearts during ischaemia actually increased ANC activity.…”
Section: Control Over the Adenine Nucleotide Carriermentioning
confidence: 93%
“…However, the effects of fatty acids on liver metabolism are multiple and difficult to disentangle at present (see Schonfeld et al, 1988;Nobes et al, 1990b). Lochner et al (1981) found that increased content of acyl-CoA in isolated rat hearts during ischaemia actually increased ANC activity.…”
Section: Control Over the Adenine Nucleotide Carriermentioning
confidence: 93%
“…The Ca2+-calmodulin complex antagonists, such as TFP, have been shown to have no effect on mitochondrial oxidative function or tissue high-energy phosphate contents [23]. In spite of that, TFP has been found to protect myocardial cells against damage resulting from the Ca 2+ paradox [24].…”
Section: Discussionmentioning
confidence: 99%
“…Normothermic ischaemic cardiac arrest (NICA) was used as model of myocar dial ischaemia [18]. After the heart was removed from the rat and arrested in ice-cold saline, the aorta was mounted onto the aortic cannula followed by retro grade perfusion using the Langendorff technique in a non-recirculating manner at 90 cm H2O pressure for 10 min at a perfusate temperature of 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The combined ox * Statistical significance (p < 0.05): NICA or NICA followed by reperfusion versus unperfused, and NICA versus NICA followed by reperfusion. [18]. It has recently been discovered that oxygen radicals contribute at least in part to the damage which occurs during myocardial ischaemia [1][2][3][4][5], As the mitochondria are organelles which utilise oxygen, it is possible that this mechanism plays an important role in the mitochondria.…”
Section: Effect Of Nica and Of Nica Followed By Reperfusion On The Acmentioning
confidence: 99%
See 1 more Smart Citation